2010
DOI: 10.1016/j.wasman.2009.10.019
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of five organic wastes regarding their behaviour during composting: Part 1, biodegradability, stabilization kinetics and temperature rise

Abstract: This paper aims to compare household waste, separated pig solids, food waste, pig slaughterhouse sludge 2 and green algae regarding their biodegradability, their stabilization kinetics and their temperature rise during 3 composting. Three experiments in lab-scale pilots (300L) were performed for each waste, each one under a 4 constant aeration rate. The aeration rates applied were comprised between 100 and 1100 L/h. The 5 biodegradability of waste was expressed as function of dry matter, organic matter, total … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
31
0
3

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(42 citation statements)
references
References 16 publications
7
31
0
3
Order By: Relevance
“…The temperature drop between peaks may be attributable to the large amount of heat loss caused by manually mixing, and some time interval was needed for heat accumulation to reach the subsequent peak. This observation is to some extent in agreement with the reports by de Guardia et al (2010a), Lee et al (2002), and Himanen and…”
Section: Changes Of Temperature Ph and Moisturesupporting
confidence: 94%
See 1 more Smart Citation
“…The temperature drop between peaks may be attributable to the large amount of heat loss caused by manually mixing, and some time interval was needed for heat accumulation to reach the subsequent peak. This observation is to some extent in agreement with the reports by de Guardia et al (2010a), Lee et al (2002), and Himanen and…”
Section: Changes Of Temperature Ph and Moisturesupporting
confidence: 94%
“…Composting is a biological process in which organic matter (OM) can be utilized by aerobic thermophilic and mesophilic microorganisms as substrate and mainly converted into mineralized products (CO 2 , H 2 O, NH 4 + ) or stabilized OM (mostly as humic substances) (Bernal et al, 2009;He et al, 2009;de Guardia et al, 2010a;de Guardia et al, 2010b). Although composting has been widely practiced with its final products being used as fertilizer or soil amendment, there are still knowledge gaps in understanding it due to the high variety and heterogeneity of feedstocks (Li et al, 2008;Himanen and Hänninen, 2011).…”
Section: China Pollution Source Census Issued By the Ministry Of Envimentioning
confidence: 99%
“…Hua et al (2008) reported a steadily decreasing trend of moisture content from an initial value of 62.5% to a final value of 30.2% after 60 days during the composting of sewage sludge mixed with rapeseed marc. Guardia et al (2010) observed a decrease in the moisture content of composted food waste with wood chips the mixture from 63.4-50.5% after 37 days of composting. Ghaly et al (2007) reported a small reduction in the moisture content (from 60-59.47%) during the bioremediation of toluene contaminated soil.…”
Section: Moisture Contentmentioning
confidence: 92%
“…Guardia et al [26] composted food waste with wood chips and observed a decrease in the moisture content of the mixture from 63.4% to 50.5% after 37 days of composting. Ghaly et al [27] reported a reduction in moisture content from 60% to 43% after 15 days of composting creosote treated wood waste.…”
Section: Moisture Contentmentioning
confidence: 99%